E-Voting Based Blockchain Mechanism Using Feature Selection Based Machine Learning - Prabakar, T.; Kanchana, S. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The issue of scalability in e-voting system is typically circumvented by the utilization at majority of the time. These components are capable of operating without needing one another in order to function, and they are even able to keep their own records independently of one another. In this paper, we develop an intelligent E-voting system that uses machine learning algorithm for feature selection to generate the QR codes. The aim is to improve the security of the QR based on features by optimal selection of features. The QR code with other registered details is stored in database via proper blockchain authentication mechanism. The simulation is conducted in python to test the efficacy of the model against various other methods and the results of simulation shows that the proposed method has a reduced computational complexity and increased accuracy on feature selection than other existing E-voting mechanisms.